Pollution Exposure and Infant Health: Evidence from Germany - Katja Coneus; C. Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper examines the impact of outdoor and indoor pollution on children's health from birth until the age of three years in Germany. We use representative data from the German Socio-Economic Panel (SOEP), combined with five air pollution levels. These data come from the Federal Environment Agency and cover the years 2002-2007. Our work offers three important contributions. Firstly, we use accurate measures for five different pollutants (CO, NO2, SO2, O3, and PM10) on a (half-)hourly basis. Secondly, we are able to follow the effect of pollution exposure on a child's health during the first three years of life, accounting for time-invariant and unobserved neighborhood and mother-specific characteristics. Thirdly, we calculate different pollution intensity measures. Instead of relying solely on mean pollution levels, we are able to use (half-)hourly pollution levels as well as indoor pollution as measurements for the total latent pollution exposure. Our results suggest a significantly negative impact for some pollutants on infant health during early childhood. In comparison to outdoor pollution, indoor pollution seems to be more harmful directly after birth, while the relationship between indoor and outdoor pollution changes later in childhood. Since smoking is one source of producing carbon monoxide and thus affects child health negatively, our results further support the advice to parents of young children not to smoke.
Keywords: I12; Q53; J13; 330; Indoor and outdoor pollution; health; early childhood; Luftverschmutzung; Rauchen; Gesundheit; Kinder; Schätzung; Deutschland